The mediation effect of multiple gestations on the association between in vitro fertilisation and severe maternal morbidities: a retrospective cohort study - Xin Sun; Jing Zhang; Jing Tan; Ya-Na Qi; Wen Wang; Gui-Ting Zhang; Kang Zou; Xing-Hui Liu (BMJ Open)
Objective To investigate whether the association between in vitro fertilisation (IVF) and severe maternal morbidity (SMM) was mediated by multiple gestations.Design A retrospective cohort study.Setting The study was conducted at six hospitals in China.Participants Pregnant women at 20 gestational weeks or longer.Outcome measure The outcome was SMM, which was a composite of potential life-threatening conditions, the use of critical medical interventions, or the status of maternal near-miss that occurred during pregnancy, childbirth or within 42 days of pregnancy termination, as defined by WHO.Results In total, 22 368 eligible pregnant women were included, among whom 497 (2.2%) received IVF, and 776 developed SMM (incidence 34.7/1000 live births, 95% CI 32.3/1000 to 37.1/1000). Four multivariable logistic regression models were constructed. Model 1, without including the variable of multiple gestations, showed that IVF was associated with higher risk of SMM (adjusted OR (aOR) 1.54, 95% CI 1.03 to 2.29). Model 2, assessing the association between IVF and multiple gestations, showed that IVF was strongly associated with multiple gestations (aOR 14.75, 95% CI 11.38 to 19.10). Model 3, by adding the variable of multiple gestations to model 1, showed that IVF was not statistically associated with SMM (aOR 0.89, 95% CI 0.58 to 1.36), but multiple gestations were associated with higher risk of SMM (aOR 5.92, 95% CI 4.88 to 7.83). Model 4, investigating the association between IVF and SMM among singleton pregnancies, showed no statistically significant association (aOR 0.70, 95% CI 0.37 to 1.32). An additional analysis by adding the interaction term of IVF by multiple gestations to model 3 showed no statistical significance of the interaction term (aOR 1.15, 95% CI 0.36 to 3.68), confirming the absence of exposure-mediator interaction.Conclusions Using the established rule for judging mediation effect, the results suggested that multiple gestations might mediate the association between the use of IVF and higher risk of SMM. Further prospective studies are warranted to test our finding.